THE EFFECT OF THE FOUR SQUARE STRATEGY ON STUDENTS’ VOCABULARY MASTERY - Nita Nurul Hidayah; Aprilia Riyana Putri (Universitas Islam Nahdlatul Ulama Jepara, 2019)
This thesis is entitled The Effect of the Four Square Strategy on Students’ Vocabulary Mastery (a-quasi experimental research at the eighth grade students of MTs. Hasyim Asy’ari Bangsri in the academic year 2018/2019). This study is to know the effect of the four square strategy on student’s vocabulary mastery. The researcher used a quasi-experiment research. This research design consists of some steps; pre-test, treatment and post-test. The sample of this study was the eighth grade students of MTs. Hasyim Asy’ari with the total was 68 students. There were three classes (8B, 8C and 8D) as participant in this study. Students of 8B was the trying out participant, then students of 8C was chosen as the Control Class and students of 8D was chosen as the Experimental Class. The Experimental Class taught by using the four square strategy. Meanwhile, the Control Class taught by conventional method. The result showed that the Experimental Class was Better than Control Class. In the pre-test, the mean score of Experimental Class was 49,058 and the Control Class was 48,588. Both of groups had increase in the mean score of post-test, the Experimental Class was higher than Control Class with the score of Experimental class was 63,058 and the Control Class was 59,764. Moreover, the result of t-test calculation showed that the t-observe was higher than t-table at 5 % significance level or 2,465> 1,66827. It means that the alternative hypothesis (Ha) was accepted and the nul hypothesis (Ho) was rejected. It could be interpreted that there was significant different between students who were taught by using the four square strategy in students’ vocabulary mastery than who were not taught using the four square strategy.